2015
DOI: 10.1039/c5nr02386f
|View full text |Cite
|
Sign up to set email alerts
|

Morphology-dependent photocatalytic activity of octahedral anatase particles prepared by ultrasonication–hydrothermal reaction of titanates

Abstract: Octahedral anatase particles (OAPs) were prepared by an ultrasonication (US)-hydrothermal (HT) reaction of partially proton-exchanged potassium titanate nanowires (TNWs). The structural/physical properties of OAP-containing samples, including specific surface area, crystallinity, crystallite size, particle aspect ratio, composition and total OAP content, were analyzed. Photocatalytic activities of samples were measured under irradiation (>290 nm) for oxidative decomposition of acetic acid (CO2 system) and dehy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
69
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(76 citation statements)
references
References 57 publications
6
69
1
Order By: Relevance
“…In the present study, platinum particles were deposited on both facets of DAPs ( Figure S9, supplementary data) and their photocatalytic activity in H 2 system was significantly higher than OAPs prepared according to ref. 53. The results of present study, however, suggested that the activity dependence cannot be simply interpreted by the exposure of facets and/or platinum deposit location, considering the influence of the content of particles with mounds.…”
Section: Photocatalytic Activitymentioning
confidence: 67%
See 1 more Smart Citation
“…In the present study, platinum particles were deposited on both facets of DAPs ( Figure S9, supplementary data) and their photocatalytic activity in H 2 system was significantly higher than OAPs prepared according to ref. 53. The results of present study, however, suggested that the activity dependence cannot be simply interpreted by the exposure of facets and/or platinum deposit location, considering the influence of the content of particles with mounds.…”
Section: Photocatalytic Activitymentioning
confidence: 67%
“…It is thought that alcohol molecules would be more easily adsorbed on the {001} facet (more reactive one with 100% five-coordinated Ti (Ti 5c ) atoms) [24] or/and better separation of charge carriers (by simultaneous transfer of electrons and holes to different facets) could facilitate redox reactions, as was reported for DAPs possessing naked {001} and Pt-modified {101} facets [52]. It was reported that DAPs possessing Pt nanoparticles uniformly deposited on both facets showed much lower photocatalytic activity than that of DAPs with Pt nanoparticles selectively deposited on {101} facets [52], similar to less active OAPs possessing only {101} facets [53]. In the present study, platinum particles were deposited on both facets of DAPs ( Figure S9, supplementary data) and their photocatalytic activity in H 2 system was significantly higher than OAPs prepared according to ref.…”
Section: Photocatalytic Activitymentioning
confidence: 97%
“…Octahedral anatase particles (OAPs), which expose eight equivalent and thermodynamically stable (1 0 1) facets, exhibit a very high level of photocatalytic activity, probably due to the preferential distribution of shallow electron traps (ETs) rather than deep ETs that results in a low rate of recombination of charge carriers [55], [56]. Although OAPs have a high level of photocatalytic activity, they are inactive under visible light (as is bare titania).…”
Section: Introductionmentioning
confidence: 99%
“…The photocatalytic performance of Cu2O@TiO2 polyhedra was different with that of pure Cu2O polyhedra without TiO2 shells, which could be attributed to the different driving forces for the charge carrier separation [105]. It is well known that controlled morphology by application of exposed facets (faceted semiconductors) significantly enhances photocatalytic performance, due to excellent crystallinity and low content of defects, e.g., octahedral and decahedral anatase particles [103,104]. Therefore, it is not surprising that similar concept was applied for copper oxide-titania heterojunction systems.…”
Section: Cu 2 O-tio 2 Heterojunctionmentioning
confidence: 99%
“…After shutting off the irradiation, these trapped electrons could be gradually released from TiO 2 to react with O 2 producing reactive radicals, which imparted the photocatalytic memory effect to Cu 2 O-NS/TiO 2 -NI photocatalyst ( Figure 15) [102]. It is well known that controlled morphology by application of exposed facets (faceted semiconductors) significantly enhances photocatalytic performance, due to excellent crystallinity and low content of defects, e.g., octahedral and decahedral anatase particles [103,104]. Therefore, it is not surprising that similar concept was applied for copper oxide-titania heterojunction systems.…”
Section: Cu 2 O-tio 2 Heterojunctionmentioning
confidence: 99%